Elevated X-Box Binding Protein1 Splicing and Interleukin-17A Expression Are Associated With Active Generalized Vitiligo in Gujarat Population - Jadeja, Shahnawaz D.; Vaishnav, Jayvadan; Bharti, Ankit H.; Begum, Rasheedunnisa (Frontiers in immunology, 2022)
Vitiligo is an autoimmune skin disorder defined by the destruction of functional epidermal melanocytes. It is a multifactorial and polygenic disorder caused due to oxidative stress, endoplasmic reticulum (ER) stress, and autoimmunity, among other factors. In the present study, we aimed to investigate the association of X-box Binding Protein 1 (XBP1) and Interleukin-17A (IL-17A) polymorphisms and monitor their systemic as well as skin expression levels in vitiligo patients from Gujarat population in India. XBP1 rs2269577 G/C, IL17A rs2275913 G/A and IL17A rs8193036 C/T polymorphisms were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method in 312 controls and 276 vitiligo patients. Transcript levels of spliced ( sXBP1 ), unspliced XBP1 ( uXBP1 ) and IL17A from peripheral blood mononuclear cells (PBMCs) as well as spliced and unspliced XBP1 from skin samples were analyzed by qPCR. IL-17A protein levels in suction-induced blister fluid (SBF) from the skin of study subjects were estimated by ELISA. The results revealed that genotype ( p =0.010) and allele ( p =0.014) frequencies of XBP1 rs2269577 G/C polymorphism were significantly different, however, no significant difference was observed in frequencies of IL17A rs2275913 G/A and IL17A rs8193036 C/T polymorphisms in control and patient population. Gene expression analysis revealed that sXBP1 and IL17A levels were significantly higher in PBMCs of generalized ( p =0.030 and p =0.039, respectively) and active ( p =0.024 and p =0.017, respectively) vitiligo patients. Moreover, we observed a significantly elevated sXBP1 expression ( p =0.037) as well as IL-17A protein levels ( p =0.009) in perilesional skin of vitiligo patients as compared to controls. Overall, these findings suggest XBP1 and IL17A play an important role in vitiligo and further substantiate the involvement of ER stress in exacerbating immune-mediated vitiligo pathogenesis.